Pushover Analysis and Incremental Dynamic Analysis of Steel Braced Reinforced Concrete Frames - Hamadamin, Sangar Saud (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
The recent earthquakes in some part of the world showed the disastrous effect on civilian areas. Most of the existing RC buildings designed only considering gravity loads without seismic design criteria. Therefore, an accurate knowledge is extremely necessary for those buildings that need seismic retrofitting. Steel bracing system can be considered as the most reasonable solution for seismic performance enhancing of RC buildings. The use of steel braces for retrofitting or strengthening seismically deficient RC frame is a reasonable solution for upgrading seismic resistance. Steel bracing is easy to erect, has the flexibility to design for meeting the required stiffness and strength, occupies less space, and economical. This study discusses the seismic behavior of RC buildings strengthened with various types of concentric steel braces, Diagonal-braced, Inverted V-braced, Zipper-braced, and X-braced. The models that have been studied are 3-storey, 6-storey, 9-storey and 12-storey buildings of which are designed by using Etabs. The static pushover analysis and incremental dynamic analysis have been conducted utilizing Seismostruct software to estimate the lateral capacity and compare the results of all the frames and bracing types. It is observed that adding braces upgrade the global capacity of the buildings in terms of lateral load capacity, displacement and stiffness compared to the cases with no bracing, and the X-braced systems performed much better than the other types of bracing. Keywords: Earthquake, Seismic design, Retrofitting, Steel bracing, Pushover analysis, Incremental dynamic analysis.

ÖZ : Dünyanın bazıbölgelerinde son depremler sivil alanlarda çokbüyük can kayıplarına sebep olmuştur. Mevcut betonarme binaların çoğu sismik tasarım kriterleri olmadan sadece düşey yükler düşünülerek tasarlanmıştır. Bu nedenle, güçlendirme gerektiren bina stoğunun saptanması son derece önemlidir. Betonarme binalarda çelik çaprazlarla yapılacak bir güçlendirme sismik performansı artırmak için en makul çözüm olarak Kabul edilebilir. Çelik çaprazlarla güçlendirme ekonomik, uygulanması kolay, alan tasarrufu ve istenilen performansa kolayca ulaşılmasını sağlar. Bu çalışma diyagonel, ters V, zipper ve X çaprazlarıyla güçlendirilmiş çerçevelerin deprem davranışını incelemektedir. Seçilen 3, 6, 9 ve 12 katlı yapılar Etabs programı tarafından tasarlanmıştır. Statik itme ve artımsal dinamik analiz (IDA) yöntemleriyle yapılan analizler ve karşılaştırmalar Seismostruct yazılımı kullanılarak yapılmıştır.Sonuç olarak betonarme binalardaki çelik çaprazların bina deprem performansını ve rijitliğini çelik çaprazsız sistemlere oranla büyük ölçüde artırdığıve X-çaprazlı sistemlerin diğerlerine gore daha iyi performans sergilediği gözlenmiştir. Anahtarkelimeler: Deprem, sismik dizayn, güçlendirme, çelik çaprazlar, static itme analizi, artımsal dinamik analiz.
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2014. Supervisor: Assist. Prof. Dr. Giray Özay.
Keywords: Civil Engineering; Earthquake resistant design; Earthquake resistant design - Concrete construction - Reinforced concrete; Buildings - Earthquake effects; Reinforced concrete - Reinforced concrete construction; Earthquake; Seismic design; Retrofitting; Steel bracing; Pushover analysis; Incremental dynamic analysis